Calorie-restricted diet mitigates weight gain and metabolic abnormalities in obese women with schizophrenia: a randomized controlled trial - Zhang, Lei; Zhu, Mingwen; Liu, Xiangqun; Zhao, Zhijun; Han, Ping; Lv, Luxian; Yang, Chun; Han, Yong (Frontiers in Nutrition, 2023)
Background: Obesity is a prevalent health problem in patients with schizophrenia, and calorie restriction diet (CRD) achieved effective weight loss and metabolic improvement; however, these have not been rigorously evaluated in obese patients with schizophrenia. Objective: To measure the effects of CRD on weight loss and metabolic status in hospitalized obese women with schizophrenia during a 4-week period. Methods: Participants were randomly assigned to two groups in a 1:1 ratio. The intervention group (n = 47) was asked to follow a CRD and the control group (n = 48) a normal diet for 4 weeks. Outcomes of body weight, body composition, as well as metabolic parameters were measured at baseline and end. Results: Forty-five participants completed the 4-week research in both the intervention and control groups. Adherence to the CRD, compared to the normal diet, body weight (p = 0.000, ηp2 = 0.424), body mass index (p = 0.000, ηp2 = 0.424), waist circumference (p = 0.02, ηp2 = 0.571), hip circumference (p = 0.000, ηp2 = 0.485), mid upper arm circumference (p = 0.000, ηp2 = 0.197), triceps skin-fold thickness (p = 0.000, ηp2 = 0.469), fat mass (p = 0.000, ηp2 = 0.304), free fat mass (p = 0.000, ηp2 = 0.145) significantly decreased with large effect size and total cholesterol (p = 0.028, ηp2 = 0.054) significantly decreased with medium effect size. There were no changes in fasting blood-glucose (p = 0.361, ηp2 = 0.469), triglycerides (p = 0.076, ηp2 = 0.036), high density lipoprotein-cholesterol (p = 0.132, ηp2 = 0.026), low density lipoprotein-cholesterol (p = 0.100, ηp2 = 0.031), as well as systolic blood pressure (p = 0.079, ηp2 = 0.035) and diastolic blood pressure (p = 0.219, ηp2 = 0.017). Conclusions: CRD is an effective lifestyle intervention strategy to reduce body weight and improve physical metabolism in hospitalized obese women with schizophrenia. Clinical trial registration: This study was registered at the Chinese Clinical Trials Registry (http://www.chictr.org.cn) with the registration number ChiCTR-INR-16009185 (data: September 10, 2016).